Določitev galne kisline, pirokatehola, floroglucinola, resorcinola in katehina s tankoplastno kromatografijo - Poljanšek, Ida (Zbornik gozdarstva in lesarstva, 2011)
The suitability of six solvent systems for the thin-layer chromatographic separation of simple phenolic compounds such as gallic acid, pyrocatechol phloroglucinol, resorcinol and related compound catechin were investigated. The most appropriate developing solvent systems for the separation of these organic compounds were chloroform - ethyl acetate - acetic acid (50 : 50 : 1) and toluene -acetonitrile - formic acid (70 : 30 : 1). The best separation of the five organic compounds was achieved using solvents with higher organic content. Detection was carried out using ferric chloride reagent and vanillin-sulphuric reagent.
Keywords: fenolne spojine; tankoplastna kromatografija; topila